Challenges Before Cooperative Thrift and Credit Societies in the Globalised Era with Reference to Disbursement of Loan - Edwin Gnanadhas, M.; Geetha, P. (Indian Journal of Finance, 2008)
Cooperatives occupy a place of eminence in the economic activity of the country and have been acting as a catalyst for socio-economic development. Since independence, the cooperative sector has made remarkable progress which has also resulted in certain weaknesses. If the cooperative sector fails to adopt itself to the new environment, it may not survive. Hitherto, a majority of them existed because of government support. Globalisation of the economy, deregulation of interest rates, rapid development of information technology and introduction of prudential norms have introduced a new element of competition. In the light of this changing scenario, cooperative societies have to prepare themselves to face these challenges.Employees Cooperative Thrift and Credit society is a Non-Agricultural credit society, started mainly for saving the employees from the hands of moneylenders. Important income of the society is the interest on loans. But the main problem is delays in sanctioning of loans by the societies. So the present study attempts to study the delays in sanctioning of loans by the societies. Factor analysis is used to analyze the reasons for delays in sanctioning of loans.The present study reports that the Employees Cooperative Thrift and Credit Societies are not in a condition to face the challenges posed by development in the national and international economy. The apex cooperative institutions, therefore, should come forward for the revival of the societies in order to make them economically viable.